Treatment of advanced melanoma - A changing landscape - Hepner,Adriana (2017)
Summary Following decades of relative ostracism, advances in the treatment of melanoma have brought a new reality for patients, physicians and researchers. While antibodies targeting molecules involved in the modulation of the interaction between melanoma and immune cells changed the meaning of the term “cancer immunotherapy,” a better characterization of the molecular aberrations involved in melanoma carcinogenesis prompted the development of inhibitors of the mitogen-activated protein kinase pathway (MAPK) that also led to significant improvements both in response rates and survival. As a result, new drugs have been approved for clinical use in the United States and Europe, including the immune-checkpoint blockers ipilmumab, pembrolizumab and nivolumab, the oncolytic herpesvirus talimogene laherparepvec, and the targeted-agents vemurafenib, dabrafenib, cobimetinib and trametinib. In this article, we review the results of studies that brought new approaches to the bedside and discuss how these developments are being incorporated into the care of patients in Brazil.